PENGARUH GEOGRAFIS KEHIDUPAN MASYARAKAT SUKU SAMIN DI KABUPATEN BOJONEGORO SEBAGAI PEMBELAJARAN IPS MATERI KERAGAMAN BUDAYA - Ita Aristia Sa’ida (Universitas Islam Lamongan, 2018)
The Samin community which has various traditions and cultures can be categorized as one of the ethnic groups in Indonesia. The Samin community is a group of people who follow the Samin Surosentiko teachings that emerged during the Dutch colonial period. As one of the ethnic groups in Indonesia, the Samin community has cultural values that are different from other communities. For more than 100 years the Samin people have experienced changes in the social and cultural institutions that they have been following. Samin community life is influenced by the geographical conditions of the area where they live. So what they do must have something to do with the nature where they live. This research was conducted at the Samin community in Japanese Village, Margomulyo Sub-district, Bojonegoro District, using descriptive qualitative research. the analysis process will be carried out using an interactive analysis model (Miles and Huberman in Sutopo, 2002). In this analysis model, the three components of the analysis are: data reduction, data presentation, and drawing conclusions or verification. So the results obtained in this study are to know the ability of the Samin community to interact with the environment and nature that deserves to be appreciated. The Samin community in its development has gone through various kinds of pressures, especially external pressures. Limited geographical conditions and also distant areas make the Samin community try hard and optimistic to survive.